The impact of tumor invasion to muscularis mucosaevascular plexus on patient outcome in pT1 bladder urothelial carcinoma - (:unkn) unknown (My University, 2020)
Objectives: T1 bladder cancer has a wide range of tumor behavior and lamina propria invasion depth has a high potential risk of disease progression. To evaluate the patient outcome according to the tumor invasion to the muscularis mucosae-vascular plexus (MM-VP) in pT1 bladder urothelial carcinoma (BUC). Materials and methods: This study is a retrospective analysis of patients consecutively recorded from 2007 to 2013. A total of 93 patients with a history of primary pT1 BUC and complete follow-up were included. We used a pathological substaging system according to the tumor invasion regarding the MM-VP: pT1a (invasion above MM-VP) and pT1b (MM-VP invasion). We evaluated recurrence-free survival (RFS), progression- free survival (PFS), disease-specific-survival (DSS) based on this sub-staging system. Results: Pathological evaluation regarding the MM-VP invasion revealed 53 patients (57%) as pT1a BUC and 40 patients (43%) as pT1b BUC. The mean follow-up was 78.8 months. During the follow-up period; 60 patients (64.5%) had tumor recurrences, 32 patients (34.4%) had progression to invasive disease, 18 patients (19.4 %) died during follow-up related to the BUC. In 29 (54.7%) of pT1a and in 31(77.5%) of pT1b tumors, the recurrent disease was recorded during the followup period (p = 0.023). DSS rates at 5 years for pT1a and pT1b were 80.2% and 60.8%, respectively. PFS, RFS, and DSS rates were similar for pT1a/pT1b and did not reach statistical significance (p > 0.05). Conclusions: Sub-staging of pT1 BUC according to the MM-VP invasion showed a limited impact on the outcome in our patient cohort. However, the presence of pT1b disease caused a significantly higher rate of recurrence.